2017
DOI: 10.17957/ijab/15.0267
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Quinoa Accessions for Salt Tolerance in Soilless Culture

Abstract: Pakistan has more than 6 million hectares of salt affected land and quinoa is tested as a facultative halophyte having super food characteristics. A hydroponic study was conducted to explore salt tolerance of two quinoa accessions, Ames-13737 (Q7) and PI-634919 (Q9) under a range of NaCl levels (0, 100, 200 and 300 mM) in wirehouse during 2016. Plant nursery was raised, and at four leaf stage, the seedlings were transferred to plastic tubs containing 20 L half strength Hoagland's solution as nutrient source. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…The accumulation of compatible solutes, such as proline and total phenolics, is associated with salt tolerance in quinoa [51,59,125,131,132,158,159]. However, Ismail et al, (2016) showed that proline may not play a major role in either osmotic adjustment or in the tissue tolerance mechanism [160].…”
Section: Salinitymentioning
confidence: 99%
“…The accumulation of compatible solutes, such as proline and total phenolics, is associated with salt tolerance in quinoa [51,59,125,131,132,158,159]. However, Ismail et al, (2016) showed that proline may not play a major role in either osmotic adjustment or in the tissue tolerance mechanism [160].…”
Section: Salinitymentioning
confidence: 99%
“…Quinoa has been identified as a facultative halophyte with better salt tolerance [47] and a high variability in salinity tolerance among quinoa genotypes has been reported [48][49][50]. Saleem et al [51] investigated the salt tolerance behavior of various quinoa lines grown hydroponically at 100 mM NaCl salinity level and found that Q7 and Q9 lines had better chlorophyll content index, free proline, ascorbic acid, and carotenoids contents but gaseous exchange traits decreased in Q7 plants under saline environment. In another study, Iqbal et al [34] found an improvement in water relations, leaf photosynthetic rate, K + contents in leaf, proline, phenolics, morphological and yield related attributes and ultimately increased grain yield at 10 dS m −1 .…”
Section: Abiotic Stressesmentioning
confidence: 99%
“…Quinoa possesses several defenses against high salt concentrations, including enhanced tolerance to reactive oxygen species (ROS), effective regulation of Na + storage in leaf vacuoles, and efficient xylem Na + loading [14]. The accumulation of appropriate solutes, such as proline and total phenolics, is also associated with salt tolerance in quinoa [15]. Moreover, antioxidant enzyme activities in quinoa were shown to be influenced by the extent of salinity.…”
Section: Introductionmentioning
confidence: 99%